Association between patient activity and long-term cardiac death in patients with implantable cardioverter-defibrillators and cardiac resynchronization therapy defibrillators. (29th August 2020) - Zhao, Shuang; Chen, Keping; Su, Yangang; Hua, Wei; Chen, Silin; Liang, Zhaoguang; Xu, Wei; Dai, Yan; Liu, Zhimin; Fan, Xiaohan; Hou, Cuihong; Zhang, Shu
Abstract: Background: Patient activity (PA) has been demonstrated to predict all-cause mortality. However, the association between PA and cardiac death is unclear. Aims: The aims of this study were to determine whether PA can predict cardiac death and what is the cut-off of PA to discriminate cardiac death, as well as the mechanism underlying the relationship between PA and survival in patients with home monitoring. Methods: This study retrospectively analysed clinical and implantable cardioverter-defibrillator/cardiac resynchronization therapy defibrillator device data in 845 patients. Data regarding PA and PP variability during the first 30–60 days of home monitoring were collected, and mean values were calculated. The primary endpoint was cardiac death, and the secondary endpoint was all-cause mortality. Results: The mean PA percentage was 11 ± 5.8%. Based on receiver operating characteristic curve analysis, we determined that a PA cut-off value of 7.84% (113 min) can predict cardiac death. During a mean follow-up period of 31.1 ± 12.9 months (ranging from three to 60 months), PA ≤ 7.84% was associated with increased risks of cardiac death in an unadjusted analysis; after adjusting in a multivariate Cox model, the relationship remained significant between PA≤7.84% and cardiac death (hazard ratio = 3.644, 95% confidence interval = 2.424–5.477, p < 0.001). Moreover, a significant correlation was observed between PA and PP variability ( r = 0.601, p < 0.001). Conclusions: A baseline PA ≤ 7.84% was associated with a higher risk of cardiac death in patients who have survived more than three months after implantable cardioverter-defibrillator/cardiac resynchronization therapy defibrillator implantation. PA had a sizable effect on heart rate variability, reflecting autonomic function.